Co-operatives in a Global Economy: The Challenges of Co-operation Across Borders - Reed, Darryl; McMurtry, J. J. (Cambridge Scholars Publishing, 2008)
In their efforts to internationalize in the emerging global economy, co-operatives not only face a variety of problems that are common to all firms, but encounter specific challenges due to their particular value commitments, forms of incorporation and organizational structures. These features of cooperatives are generally seen as a major source of competitive disadvantages and may cause significant trade-offs, forcing cooperatives to choose between living up to their principles of member ownership and control and remaining economically viable. Critics argue that such trade-offs signal the increasing irrelevance of cooperatives in a global economy. Advocates, however, counter that cooperatives may have unique competitive advantages which can be exploited in a global economy and that current trade-offs facing cooperatives can be overcome with the development of new international and transnational cooperative institutions and practices. Cooperatives, they claim, represent a much more sustainable and equitable form of production and may form the basis for viable, alternative approaches to development. This collection examines these debates about the roles of cooperatives in our increasingly global economy.
Keywords: business & economics; business & economics - international; co-operatives; globalization; social economy; social science - developing and emerging countries

The Institutions of the Market: Organizations, Social Systems, and Governance - Ebner, Alexander; Beck, Nikolaus (OUP Oxford, 2008)
This book approaches markets as a dynamic ensemble of institutions; and as a set of rules or norms, that contribute to the evolution of social systems of governance, and can be analysed as a structured social system. It tackles such questions as: * Where do markets come from and what drives their evolution? * How do organizations cope with the competitive dynamism of markets? * What is the role of governance mechanisms in the institutional coordination of markets? Using this 'new institutionalist' approach, an international group of leading scholars examine the institutional foundations of economic change. Drawn from an array of disciplines, including Business, Organization Studies, Economics, and Sociology, the contributors address the organizational capabilities of firms, the social structuration of competition, and the diversity of governance mechanisms in the market. Contributors include: Nikolaus Beck, Christophe Boone, Robert Boyer, Alexander Ebner, Neil Fligstein, Henrich R. Greve, John Harriss, Bob Hinings, Geoffrey M. Hodgson, Bob Jessop, Alfred Kieser, Namrata Malhotra, Renate E. Meyer, Richard R. Nelson, Rudolf Richter, Peter Walgenbach, Filippo Carlo Wezel, Sidney G. Winter, and Arjen Van Witteloostuijn.
Keywords: business & economics; competitive dynamism; economics; evolution of markets; governance mechanisms; institutional coordination; management; markets; new institutionalist approach; organizational capabilities; social structuration

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Keywords: ARENDT, Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).

America transformed: globalization, inequality, and power - Hytrek, Gary J.; Zentgraf, Kristine M. (Oxford University Press, Incorporated, 2008)
Globalization--the interconnection of the world culturally, socially, politically, and economically--has generated intense theoretical and practical concerns. Is globalization inevitable? What are the effects of globalization on social structures and individual perceptions? What is the effect of globalization on societal level inequality? America Transformed: Globalization, Inequality, and Power examines these questions by analyzing the links among global processes and shifting patterns of stratification, inequality, and social mobility in the United States. While many texts separate discussions of macro- and micro-level processes when examining globalization, this book skillfully integrates general macro-level processes with specific reference to the micro-level effects of globalization in the U.S. Exploring the critical dimensions of inequality--class, gender, and immigration--America Transformed situates the U.S. experience within the broader global context, and fleshes out the mechanism through which global processes affect social stratification. By examining the social construction of globalization, the authors identify the key policy challenges of globalization, and some of the innovative community-based responses to social inequality.America Transformed provides powerful insights into the contested dialectical relationship between global and local forces: how globalization shapes stratification and inequality in the U.S., and how local communities attempt to mediate those changes.
Keywords: globalization; social classes; social science / sociology / general